Research of Models for Evaluating the Optimal Level of Information Security Investment - A. S. Polyakova (Безопасность информационных технологий, 2012)
This article presents a research of Gordon—Loeb model for evaluating the optimal level of information security investment and a model of interdependent risks. One is provided by practical recommendations for choosing and applying models, for choosing a range of vulnerabilities to concentrate financial resources on, and weak points of models are discussed.